Analisis Sikap Berbudi Luhur Melalui Filosofi Memayu Hayuning Bawono Perspektif Kontruksi Sosial Peter Ludwig Berger (Studi Kasus di PSHT Komisariat IAIN Ponorogo) - Habib Mujahidin Ma’sum; Abu Muslim (Ashfiya Journal of Qualitative Insight in Islamic Studies, 2025)
The background of the problem at PSHT Komisariat IAIN Ponorogo is the lack of understanding about noble character attitudes and behavior among its members. PSHT members tend to have attitudes that do not fully reflect the noble values inherent in the teachings of Setia Hati Terate martial arts. The cause of this problem is that members often feel superior due to their martial arts training, which involves physical and mental discipline, leading to a sense of being the best among others. Martial arts teachings typically incorporate noble values that have been guiding principles for centuries, given that martial arts are a national heritage worth preserving. To address the lack of awareness among members about the importance of noble character attitudes, PSHT Komisariat IAIN Ponorogo incorporates habituation practices that implement noble character attitudes through the philosophy of "Memayu Hayuning Bawana" during training sessions. This research aims to investigate two primary objectives (1) To examine the understanding and implementation of noble values embedded in the "Memayu Hayuning Bawana" concept among PSHT members at Komisariat IAIN Ponorogo. (2) To explore the implications of implementing these noble values on the members of PSHT Komisariat IAIN Ponorogo. This study adopts a qualitative research approach, gathering data through in-depth interviews and observational techniques. The theoretical framework is grounded in Peter L. Berger's social construction theory, which provides insight into the formation of noble character attitudes through social interactions. Based on the data analysis, it was found that (1) The implementation of noble character attitudes through the "Memayu Hayuning Bawana" philosophy at PSHT Komisariat IAIN Ponorogo occurs during training and shapes positive attitudes through social interaction. (2) This implementation fosters positive attitudes among members, including: a culture of greeting and respect, brotherhood, good speech, tolerance, and responsibility.